Prinosi iseljeništva uspostavi hrvatske države - Jurčević, Josip, povjesničar (2006)
Croatia's emigrants made a massive contribution to establishing an independent Croatian state earning thereby a significant place in recent Croatian history. Croatia is among a group of European countries from which a process of emigration was ongoing throughout the entire 20th century. Since the vast majority of emigrant Croats left their Homeland against their wills, desires or convictions, it is understandable that they endeavoured to maintain a bond with the Homeland. This is can be best seen insofar as the organised forms of social, cultural, religious and political life in the emigration are rooted in the Croatian national identity. Organised Croatian emigrant life, however, besides nurturing identity and memories, had the objective of, as directly and as intensively as possible, working towards a change of the situation in the Homeland. Several decades of continued and intensive state-building activity in emigrant Croatia lead to a political maturity in the Croatian emigration that made it a community fully prepared to actively participate in the massive historic changes that, at the end of the 1980's, began more and more rapidly to unfold across eastern Europe and in the Croatian lands.
Summary ; resumen
Keywords: Hrvati -- Emigranti -- Nacionalni identitet -- Patriotizam